Rancang Bangun Media Pembelajaran Sistem Operasi Jaringan Materi Instalasi Debian Berbasis Android - Dol Frialdo; Annisa Helmina; Eka Oktaviani Melianti; Nizwardi Jalinus; Rijal Abdullah (Journal on Education, 2023)
The design of learning media for network operating system installation material for Android-based Debian is a design for a learning application that aims to assist users in understanding Debian installation material, a network operating system. This application will present material interactively and use various features such as text, images and videos to make it easier for users to understand. In addition, this application will also be equipped with practice questions to test mastery of the material that has been studied. Thus, this application is expected to help users learn the Debian installation material in an effective and enjoyable way.